Russia's evolution toward a unified strategic operation the influence of geography and conventional capacity - Reach, Clinton Bruce; Demus, Alyssa; Grisé, Michelle (RAND Corporation, 2023)
"For decades, the Russian military has been faced with the same problem: how to overcome the North Atlantic Treaty Organization's (NATO's) strategic depth in a time of strategic nuclear parity. In the late Soviet era, this was done by building up massive numbers of ground forces to overcome prepared defenses. In 2008, Russia drastically reduced its land forces in the hopes that long-range strike could compensate for a lack of mass on the ground in a regional war. Russian strategists have since focused on the ways and means through which Russia can conduct offensive actions throughout the entire depth of NATO without large numbers of ground forces. As of 2021, Russia was still reliant to some degree on nonstrategic nuclear weapons (NSNW) for regional warfighting. Recent evidence suggests that Russian planning for regional war is trending toward a unified strategic operation. This notional concept is intended to more effectively organize and allocate Russia's conventional strike and nonkinetic attack capacity as it fills the role of Russian NSNW in regional war over the coming decades. To understand why this trend is occurring, this report examined Russia's evolution toward a unified strategic operation and associated capability development, focusing on four areas: long-range conventional strikes against critical military and civilian targets; electronic warfare (EW) to disrupt NATO command, control, communications, computers, intelligence, surveillance, and reconnaissance; counterspace actions; and cyberattacks against critical infrastructure."
Keywords: Military planning / Russia (Federation); Ballistic missiles; Nuclear weapons; Information warfare; Space warfare; Unified operations (Military science); Russia (Federation) / Military policy; Military planning; Military policy; Russia (Federation)